2002
DOI: 10.1590/s0037-86822002000100011
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical reaction to the treatment of tuberculosis uncovering previously silent meningeal disease

Abstract: The development of paradoxical clinical worsening following initiation of tuberculosis treatment may complicate the clinical course of both HIV-infected and uninfected patients. We report a severe manifestation of the so called paradoxical reaction to the treatment of tuberculosis that unmasked previously silent meningeal disease in a 34-year-old HIV-infected male patient. Key-words: AIDS. Antiretroviral therapy. Paradoxical reaction. Tuberculosis. Tuberculous meningitis.Resumo O desenvolvimento de piora clíni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(6 reference statements)
0
4
0
1
Order By: Relevance
“…4 The worsening of TB symptomatology and lesions in response to ATT has previously been reported and called ''paradoxical reaction'' by some investigators. 5,6,7 Since the first report of paradoxical reaction in 1890 by Robert Koch, the paradoxical worsening of tuberculosis after initiation of ATT has been well documented in systemic TB, including intracranial tuberculomas, 8 meningeal disease, 9 tuberculous meningeal radiculitis 10 and pleural effusion. 11 However, ocular paradoxical worsening associated with TB has been reported only rarely.…”
mentioning
confidence: 99%
“…4 The worsening of TB symptomatology and lesions in response to ATT has previously been reported and called ''paradoxical reaction'' by some investigators. 5,6,7 Since the first report of paradoxical reaction in 1890 by Robert Koch, the paradoxical worsening of tuberculosis after initiation of ATT has been well documented in systemic TB, including intracranial tuberculomas, 8 meningeal disease, 9 tuberculous meningeal radiculitis 10 and pleural effusion. 11 However, ocular paradoxical worsening associated with TB has been reported only rarely.…”
mentioning
confidence: 99%
“…. Paradoxical worsening of pre-existing pulmonary and extrapulmonary tuberculosis has been increasingly reported in HIV-positive patients, which produces a diagnostic challenge to caring infectious disease and respiratory physicians [5,6,7,8,9,10,11,12,13,14,15,16]. In recent studies, this condition was found in 11-36% of patients receiving highly active antiretroviral therapy (HAART) [7,8,15].…”
mentioning
confidence: 99%
“…Generally, paradoxical worsening does not require a change of therapeutic regimen, but our case required a change. Most cases of paradoxical worsening in patients with intracranial tuberculosis are caused by tuberculomas in the brain parenchyma [8], and there are few reports of paradoxical worsening in tuberculous meningitis [13].…”
Section: Discussionmentioning
confidence: 99%